Resource competition between spotted hyaenas, Crocuta crocuta, (Erxleben 1777), and brown hyaenas, Parahyaena brunnea, (Thunberg 1820) - Millar, Robert P. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.